Work, Sex and Power The Forces that Shaped Our History - Thompson, Willie (Pluto Press, 2015)
This is the history of the world, from the origins of the Cosmos to the present day, seen through three major narratives: work, sex and power - the forces that have done more than any other to shape the world as we see it now. It expertly explores the foundations of our developing society by showing how these grand themes have recurred throughout the various phases of global history. From communities of Palaeolithic hunter-gatherers, through feudalism and onto the capitalistic machine-civilisation of recent centuries, Willie Thompson takes us on a journey that is fundamentally opposed to mainstream histories which concentrate on monarchs, politicians and military commanders. At the centre of this book lies the interaction between humans and their environment. By exploring history in this way, it reveals a simple yet powerful materialist understanding of how we got to where we are today, and opens a door to a different reading of our world.